Genetic Diversity of Echinococcus granulosus in Southwest China Determined by the Mitochondrial NADH Dehydrogenase Subunit 2 Gene - Jiahai Wang; Ning Wang; Dandan Hu; Xiuqin Zhong; Shuxian Wang; Xiaobin Gu; Xuerong Peng; Guangyou Yang (The Scientific World Journal)
We evaluated genetic diversity and structure of Echinococcus granulosus by analyzing the complete mitochondrial NADH dehydrogenase subunit 2 (ND2) gene in 51 isolates of E. granulosus sensu stricto metacestodes collected at three locations in this region. We detected 19 haplotypes, which formed a distinct clade with the standard sheep strain (G1). Hence, all 51 isolates were identified as E. granulosus sensu stricto (G1–G3). Genetic relationships among haplotypes were not associated with geographical divisions, and fixation indices (Fst) among sampling localities were low. Hence, regional populations of E. granulosus in the southwest China are not differentiated, as gene flow among them remains high. This information is important for formulating unified region-wide prevention and control measures. We found large negative Fu’s Fs and Tajima’s D values and a unimodal mismatch distribution, indicating that the population has undergone a demographic expansion. We observed high genetic diversity among the E. granulosus s. s. isolates, indicating that the parasite population in this important bioregion is genetically robust and likely to survive and spread. The data from this study will prove valuable for future studies focusing on improving diagnosis and prevention methods and developing robust control strategies.